A manifestação oculta da criação nos jogos de negócio - Silva, Maria Elisa Toledo da (2010)
This paper aims to depict digital business games as a space of creation - a concept arisen from the theories of the English psychoanalyst Donald Woods Winnicott. He said that the space of creation allows a shared relationship between the individual and the reality around him, and structures unique approaches based on the way every human being presents himself in face of everyday situations. In addition to this concept, this paper focuses on the analysis of relevant integration of games with business education programs in corporate business. Through these games, a professional is faced with many complex situations presented throughout daily life, related to wandering issues between the subject, the corporation and the society. In this context, we seek for clues that show an ulterior demonstration of creation, whereas such clues tend to function as a possible springboard to get the players/peers to develop particular cognitive structures, through practical experience and perception. We will also reflect upon Merleau-Pontyan phenomenological concepts, especially because we believe that we're dealing with spaces filled with identities and meanings and awareness to be analyzed. The dialogue proposed in this study between psychoanalysis, games and business corporations tend to contribute to shaping the meaning and the feeling of the game experience, taking into account that such environments are spaces where human creation can flourish, aiming to integrate into an ever-changing model, a continuous flowing model, in which the rhizome sets the ground for everything and makes what is about to come the gathering of several confronting thoughts in a kind of endless expansion